Full-Color Biomimetic Photonic Materials with Iridescent and Non-Iridescent Structural Colors - Kawamura, Ayaka (Sci Rep, 2016)
The beautiful structural colors in bird feathers are some of the brightest colors in nature, and some of these colors are created by arrays of melanin granules that act as both structural colors and scattering absorbers. Inspired by the color of bird feathers, high-visibility structural colors have been created by altering four variables: size, blackness, refractive index, and arrangement of the nano-elements. To control these four variables, we developed a facile method for the preparation of biomimetic core-shell particles with melanin-like polydopamine (PDA) shell layers. The size of the core-shell particles was controlled by adjusting the core polystyrene (PSt) particles’ diameter and the PDA shell thicknesses. The blackness and refractive index of the colloidal particles could be adjusted by controlling the thickness of the PDA shell. The arrangement of the particles was controlled by adjusting the surface roughness of the core-shell particles. This method enabled the production of both iridescent and non-iridescent structural colors from only one component. This simple and novel process of using core-shell particles containing PDA shell layers can be used in basic research on structural colors in nature and their practical applications.